Circularity in textile waste: Challenges and pathways to sustainability - Saloua Biyada; Jaunius Urbonavičius (Cleaner Engineering and Technology)
Emerging fast fashion concepts in the textile industry have contributed to the over-consumption of clothing and the consequent over-production of waste. Meanwhile, consciousness of the environmental pollution associated with the ongoing production and disposal of textiles has greatly expanded. For these reasons, greener and cleaner solutions are constantly being sought to remedy the negative impact of this waste on the environment sustainably. In this respect, the aim of this study is to provide an overview of the negative impact of textile waste on the environment, also the current research aimed at cleaner and more sustainable biotechnologies and to spotlight new developments in waste management strategies to remedy it. To achieve this, a literature review is provided based on data from Scopus, Web of Science and Google Scholar. The outcome of this study reveals that: i) the production of textile waste has increased significantly with the increase in clothing production; ii) the lack of rigorous environmental legislation related to the textiles production can further exacerbate the problem and contribute to increased environmental pollution; iii) the existing textile waste management programmes have proved unsuccessful; iv) clean and sustainable solutions such as biological treatment are required to overcome the harmful effects of textile waste; v) biotechnologies that use these wastes may generate valuable new products, clean energy, etc. Ultimately, overview of current-state-of-art suggests that textile waste can be successfully managed through biological treatment (using micro-organisms and especially enzymes), and thus mitigate the inappropriate textile waste management programs, thereby demonstrating the added value of the current study for the forthcoming research.